2017
DOI: 10.1136/tobaccocontrol-2016-053424
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco cessation and household spending on non-tobacco goods: results from the US Consumer Expenditure Surveys

Abstract: Households that quit tobacco spend less in areas that enable or complement their tobacco cessation, most of which may be motivated by financial strain. The most robust association between tobacco cessation and spending was the significantly lower spending on alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Our findings support the idea that expenditure on tobacco and alcohol generates opportunity costs, in that scarce resources are spent on these products that might be better spent elsewhere [37]. Most of existing studies on expenditure on tobacco have been conducted in low‐income countries; however they have found that households spending money on tobacco allocate less money to food, clothing, housing, education, energy, and transportation, communication and medical care [22,38–42].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our findings support the idea that expenditure on tobacco and alcohol generates opportunity costs, in that scarce resources are spent on these products that might be better spent elsewhere [37]. Most of existing studies on expenditure on tobacco have been conducted in low‐income countries; however they have found that households spending money on tobacco allocate less money to food, clothing, housing, education, energy, and transportation, communication and medical care [22,38–42].…”
Section: Discussionsupporting
confidence: 80%
“…Our findings suggest that the cessation or reduction of tobacco and alcohol use may alleviate household financial insecurity by increasing disposable income; however, our study was not able to show how households would reallocate these resources if so released. Longitudinal studies examining changes in expenditure patterns following cessation of either product are extremely limited; one US study has found that households that quit tobacco reduce expenditure on items that may facilitate or complement smoking cessation, such as alcohol, food, entertainment and transport [37]. This may mean that when households quit in the midst of (or due to) financial strain, they are unable to, or choose not to, reallocate spending to other areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies of mixed-age U.S. adults have found that tobacco costs can “crowd out” other necessities like food, clothing, healthcare, and rent payments (Busch et al, 2004; Baggett et al, 2016). Tobacco cessation, on the other hand, has been associated with lower spending on things that enable or complement smoking, including alcohol (Rogers et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…4 Spending household funds on cigarettes is associated with lower spending on health care, education, healthy food, and housing. [5][6][7] Previous studies have demonstrated that a significant proportion of adult cigarette smokers are interested in quitting smoking. 8 However, many of them have not been able to quit smoking successfully and experience relapse.…”
Section: Purposementioning
confidence: 99%